The Importance of Integrating Education for Sustainable Development in Global Warming Assessments to Improve Students' Critical Thinking Skills - Sri Ramadhani Dar; Emiliannur Emiliannur; Festiyed Festiyed; Selma Riyasni; Nanang Winarno (Jurnal Penelitian Pembelajaran Fisika, 2025)
This research was motivated by the fact that the assessments used in physics education still do not facilitate students' critical thinking skills. The purpose of this study was to analyze the need to develop critical thinking skills assessments integrated with Education for Sustainable Development (ESD) in physics education to support Sustainable Development Goal (SDG) 13: Climate Action. In the 21st century, students need not only conceptual understanding but also critical thinking skills to address global environmental challenges. Using a descriptive quantitative approach, this study involved 33 Grade X Phase E students through Ennis-based critical thinking tests, student questionnaires, and teacher interviews. The results showed that students' critical thinking skills were mostly in the moderate to low range, with the lowest performance on the “advanced clarification” indicator, indicating difficulty in connecting physics concepts with real-life phenomena. However, students demonstrated good sustainability awareness (71.9%–75.17%) and strong technological skills (80.57%), indicating readiness for digital-based assessment. ESD dimension analysis showed effective integration between environmental, cultural, economic, and social aspects in promoting climate action. Teacher interviews confirmed that existing assessments were inadequate in measuring critical thinking and its relationship to ESD. Therefore, the development of electronic assessments is essential to improve critical thinking and sustainability awareness on the topic of global warming. This innovation supports transformative and holistic learning that empowers students to actively contribute to achieving Sustainable Development Goal (SDG) 13 Climate Action.